Lecturer’s Performance in Java Island in Review of and Lecturer Performance in Review of Organizational Culture, Management Effectiveness and Organizational Commitment - Abrar Hiswara; Ni Nyoman Sawitri; Hapzi Hapzi; Zahara Tussoleha Rony (West Science Interdisciplinary Studies, 2023)
In the particular setting of Java Island's higher education institutions, this study explores the intricate links between organizational culture, managerial effectiveness, organizational commitment, and lecturer performance. An online questionnaire was used in this study to gather data from a sample of 267 lecturers and teaching staff members. Data analysis was done using structural equation modeling using SEM-PLS 4. The findings demonstrated that lecturers' organizational commitment and performance were greatly enhanced by a supportive and upbeat corporate culture. Effective management techniques also have a positive impact on lecturers' performance and organizational commitment. Conversely, it was discovered that increased lecturer performance was closely correlated with organizational commitment. The study's results highlight how crucial it is for higher education institutions to develop a welcoming environment, enhance management procedures, and put initiatives in place to encourage professor dedication. Despite its shortcomings, this study provides insightful information for higher education institutions in Java Island and abroad, laying the groundwork for further research in the subject of higher education management.